Translation of The Otago Exercise Program for adoption and implementation in the United States - Tiffany E Shubert; Matthew Lee eSmith; Marcia Gail Ory; Cristine eClarke; Stephanie eBomberger; Ellen eRoberts; Jan eBusby-Whitehead (Frontiers Media S.A., 2015)
.